MINISTERIAL LIABILITY IN THE ROMANIAN CONSTITUTIONAL SYSTEM - NICOLAE PAVEL (Challenges of the Knowledge Society)
What seems relevant to us for highlighting in this study is the approach of the ministerial liability within the Romanian constitutional and legal system starting with the first document of constitutional value, namely the Developing Statute of the Paris Convention of 1858 until today, that is the Constitution of Romania, revised in 2003 and republished. Having in view that this is a generous study topic covering over 150 years of constitutional and legal evolution of ministerial liability in Romania, it is necessary to specify from the very beginning the need of a diachronic approach of this topic by identifying all Romanian Constitutions that have regulated the constitutional system during this period of time. Moreover, we have to specify that, during this period of time, Romania has experienced several forms of governance, namely monarchy, people’s republic, socialist republic and semi-presidential republic. With this approach, the proposed study opens a complex and complete yet not exhaustive vision in the current scope of the ministerial liability. It is also the reason why the study begins with preliminary considerations in which the terminology used in the content of the study is justified. Following a key-scheme, there are successively examined the two major parts of the study, namely the general theory regarding the concepts of ministerial responsibility and liability and the Romanian constitutional, legal and doctrinaire milestones of the ministerial liability.